ONLINE SURGICAL TEACHING&LEARNING: Our Experience During the Pandemic - Kyi Win, Kyi; Htike, Thaung; Sze Kiat, Sim (UNIMAS, 2020)
During the pandemic and the implementation of Movement Control Order, the medical programme teaching and learning activities were significantly affected. Not only were the students not able to enter hospital facilities for clinical teaching, there have been no face-to-face lectures, seminar presentations nor Problem Based Learning (PBL) activities due to the restriction. For this reason, Year 3 MDP 30309 Surgery Posting theory teaching sessions were replaced with three weeks’ online teaching program for the total of 78 students (combined classes of two postings) starting from 9th June until 25th June 2020 and followed by the End of Posting Online Theory Exam through eLEAP platform. The format of theory papers was 20 Multiple Choice Questions, 10 Best Answer Questions and lastly, 8 Short Essay Questions. At the end of this posting, students were requested to respond to Feedback Questionnaire in the eLEAP page and allowed to express their comments and suggestions on this online teaching programme anonymously. In this article, we would like to share our online teaching experience and review of the students’ feedback.